Evaluating Debt Repurchases: What Are the Alternatives to Investment? - Cabral, Célia Costa (2019)
A general model of debt repurchases is built which reconciles most points raised in the literature on buybacks. The inclusion of assets alternative to domestic investment is shown to be of crucial importance in the analysis and leads to the reversal of some previous results. It is shown that investment necessarily rises following a buyback, independently of the source of the funds used. The condition that determines whether or not buybacks are an attractive solution to the debtor is derived. It is shown to depend on the price at which debt can be bought and on an -interest differential effect".